Implementasi Manajemen Kurikulum Merdeka Dalam Meningkatkan Mutu Pendidikan Di Sekolah Abata - Firdaus, andrian; Alfan Hadi (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
Education is a process by teachers and students when learning occurs in class. At this time, the school began implementing the independent curriculum issued by the Minister of Education, Mr Nadiem Makarim; the educational institutions at ABATA Lombok school were adjusted to the peculiarities, environmental conditions and regional potential. Implementation of Independent Curriculum Management in Improving the Quality of Education at ABATA School education involves the education unit committee and various stakeholders, including parents, organizations, and various centres, under the coordination and supervision of the Mataram City Education Office. which organizes government affairs under its authority. The research method used by the author is descriptive qualitative with a case study design. Because this study seeks to analyze how the implementation of the independent curriculum management at ABATA school Lombok that the qualitative approach is a research process that produces descriptive data in the form of written or spoken words from people or observable behaviour. The Merdeka Curriculum is expected to produce more creative, independent, and skilled students in various fields. Students are expected to prepare for a better and more successful future by developing these skills and abilities.